2018
DOI: 10.1111/jam.14057
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant production: emerging trends and promising strategies

Abstract: Biosurfactants are economically most sought after biotechnological compounds of the 21st century. However, inefficient bioprocessing has mitigated the economical commercial production of these compounds. Although much work is being done on the use of low-cost substrates for their production, a paucity of literature exists on the upcoming bioprocess optimization strategies and their successes and potential for economical biosurfactant production. This review discusses some of the latest developments and most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(126 citation statements)
references
References 83 publications
0
117
0
9
Order By: Relevance
“…; Singh et al . ). This review focuses on microbial biosurfactants and current trends in agricultural and health‐related applications.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Singh et al . ). This review focuses on microbial biosurfactants and current trends in agricultural and health‐related applications.…”
Section: Introductionmentioning
confidence: 97%
“…The focus of many reviews in the area has been on the biosurfactants themselves and indeed recent reviews include those, which have focussed specifically on applications in agriculture or industry Santos et al 2016;Singh et al 2019). This review focuses on microbial biosurfactants and current trends in agricultural and health-related applications.…”
Section: Introductionmentioning
confidence: 99%
“…The BLM precipitate was able to emulsify gasoline and diesel fuel. Biosurfactants like rhamnolipid, surfactin, emulsan are extractable by organic solvents [35, 60]. In addition our study showed that the biosurfactant excreted by Shigella sp.…”
Section: Discussionmentioning
confidence: 78%
“…They all show diverse emulsification, interfacial, and surface tension properties. These compounds are known to exhibit broad-spectrum antimicrobial activity, and different classes of biosurfactants are being used by the agricultural, oil, food, cosmetic, biotechnological, and pharmaceutical industries, as well as in a wide range of environmental remediation technologies [24,[28][29][30][31][32][33][34][35]. The review of Fenibo et al [36] offers an overview of diverse applications of biosurfactants, with emphases on petroleum biotechnology, environmental remediation, and the agriculture sector.…”
Section: Biosurfactants As Green Biocidesmentioning
confidence: 99%